THE INFLUENCE OF THE COMPANY SIZE, PROFITABILITY, AND OPERATIONS COMPLEXITY OF A COMPANY TOWARDS AUDIT REPORT LAG ON BANK PERKREDITAN RAKYAT (BPR) IN BALI PERIOD 2012-2015 - Si Luh Putu Indrayani; Ida Bagus Anom Yasa (Valid: Jurnal Ilmiah, 2016)
Audit report lag is defined as the completion time range of the audit of the financial statements in which are measured based on the number of days required to obtain an independent auditor's report, since the closing date of the financial year toward the date of independent auditor publication. The research aims to examine the impact of independent variables of company size, profitability, and company's operations complexity either partially or simultaneously toward dependent variable audit report lag. The population in this research are BPR companies in Bali listed in the OJK year 2012 to 2015. Purposive sampling method uses as a method to select the sample, based on defined criteria it produced a sample obtain of 197 observation units. The data used is secondary data derived from audited non-participant observatory Methode annual financial report. Data analysis uses on this research is the SPSS application program of multiple linear regression analysis. The results of this research show partially testing that the size and complexity of the company's operations variables have no effect on audit report lag, while the profitability has influenced towards audit report lag. The simultaneous testing concludes variable that size, profitability, and the complexity of the company's operations has influence toward audit report lag of 3,36% and the rest influenced by other variables outside the research model